Tru-cut placental site trophoblastic tumor biopsy: A novel way for diagnosis. Case report - Rodolfo Sirito; Elisabetta Guida; Valerio Rumolo; Giorgio Sirito; Daniela Pastorino (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2023)
Background: A Placental Site Trophoblastic Tumor (PSTT) is a rare form of gestational trophoblastic disease and usually manifests itself with abnormal uterine bleeding and elevated β-hCG serum levels even months or years after any antecedent pregnancy event. Typically, tumors are confined into the uterus and secrete lower levels of β-hCG compared with other Gestational Trophoblastic Neoplasia (GTN). They can be detected sonographically like heterogeneous solid mass in the uterine cavity with minimal to high vascularization, but sometimes they develop into myometrium without endometrial involvement. To the best of our knowledge, uterine biopsy is the only way to make a reliable diagnosis, but for these reasons sometimes Dilation and Curettage (D&C) or hysteroscopy are not exhaustive. Their final diagnosis is histopathological and often very difficult due to their rarity, thus many times they directly present metastasis symptoms (mainly pulmonary) or paraneoplastic syndromes. Case presentation: A 37-year-old woman with the purpose of a second pregnancy, after seven weeks of amenorrhea, complained irregular bleeding and metrorrhagia. The patient underwent transvaginal ultrasound (US) and a lesion of 50 mm was found in myometrium, its echostructure was inhomogeneous and richly vascularised (CS4) with rear acoustic reinforcement. It was associated with slightly elevated serum levels of β-hCG. The patient performed a hysteroscopy with simultaneous tru-cut biopsy of the lesion under US guidance and a placental site trophoblastic tumor was diagnosed by histological examination. Conclusion: In this paper we suggest a novel method to perform the PSTT diagnosis. A tru-cut core biopsy allows a deep and precise biopsy with less invasivity and low risk of bleeding or uterine damage. Our case study shows that the employment of this novel technique can help in the diagnosis through a targeted sampling of the myometrium even in those cases in which the endometrial cavity is not involved.